2007
DOI: 10.1016/j.neuroimage.2007.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent interpretation of words: Evidence for interactive neural processes

Abstract: The meaning of a word usually depends on the context in which it occurs. This study investigated the neural mechanisms involved in computing word meanings that change as a function of syntactic context. Current semantic processing theories suggest that word meanings are retrieved from diverse cortical regions storing sensory-motor and other types of semantic information, and are further integrated with context in left inferior frontal gyrus (LIFG). Our fMRI data indicate that brain activity in an area sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 75 publications
(106 reference statements)
8
87
1
Order By: Relevance
“…In these studies, it has been shown that the specificity of the judgment (decisions based on global semantic vs. feature-specific similarity) as well as the strength of the semantic association between probe and target (relative to probe and distracter) modulate left ventral pFC activation (Badre, Poldrack, Pare-Blagoev, Insler, & Wagner, 2005;Wagner, Pare-Blagoev, Clark, & Poldrack, 2001;Thompson-Schill, DʼEsposito, Aguirre, & Farah, 1997)-that is, a weaker association between probe and target requires a greater degree of on-line exploration of the semantic database. In addition, a number of studies that look at the processing of semantically ambiguous materials-for example, metaphors and homonymshave shown that stimuli that are inherently multifaceted (in terms of their relationship to underlying meaning) also give rise to greater processing demands with the executive semantic system (Hoenig & Scheef, 2009;Mashal, Faust, Hendler, & Jung-Beeman, 2009;Chen, Widick, & Chatterjee, 2008;Gennari, MacDonald, Postle, & Seidenberg, 2007;Shibata, Abe, Terao, & Miyamoto, 2007;Stringaris, Medford, Giampietro, Brammer, & David, 2007;Zempleni, Renken, Hoeks, Hoogduin, & Stowe, 2007;Lee & Dapretto, 2006;Rodd, Davis, & Johnsrude, 2005;Rapp, Leube, Erb, Grodd, & Kircher, 2004). These findings are unsurprising given that left ventral pFC has been implicated in a wide range of different executive processes, including task switching, resolution of proactive interference and strategic priming (Gold et al, 2006;Brass, Derrfuss, Forstmann, & Cramon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, it has been shown that the specificity of the judgment (decisions based on global semantic vs. feature-specific similarity) as well as the strength of the semantic association between probe and target (relative to probe and distracter) modulate left ventral pFC activation (Badre, Poldrack, Pare-Blagoev, Insler, & Wagner, 2005;Wagner, Pare-Blagoev, Clark, & Poldrack, 2001;Thompson-Schill, DʼEsposito, Aguirre, & Farah, 1997)-that is, a weaker association between probe and target requires a greater degree of on-line exploration of the semantic database. In addition, a number of studies that look at the processing of semantically ambiguous materials-for example, metaphors and homonymshave shown that stimuli that are inherently multifaceted (in terms of their relationship to underlying meaning) also give rise to greater processing demands with the executive semantic system (Hoenig & Scheef, 2009;Mashal, Faust, Hendler, & Jung-Beeman, 2009;Chen, Widick, & Chatterjee, 2008;Gennari, MacDonald, Postle, & Seidenberg, 2007;Shibata, Abe, Terao, & Miyamoto, 2007;Stringaris, Medford, Giampietro, Brammer, & David, 2007;Zempleni, Renken, Hoeks, Hoogduin, & Stowe, 2007;Lee & Dapretto, 2006;Rodd, Davis, & Johnsrude, 2005;Rapp, Leube, Erb, Grodd, & Kircher, 2004). These findings are unsurprising given that left ventral pFC has been implicated in a wide range of different executive processes, including task switching, resolution of proactive interference and strategic priming (Gold et al, 2006;Brass, Derrfuss, Forstmann, & Cramon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation is bolstered by the fact that the temporal lobe, shown to be an important part of the N400's distributed neural source (Elger et al, 1997;Halgren, Baudena, Heit, Clarke, Marinkovic, Chauvel et al, 1994;McCarthy, Nobre, Bentin, & Spencer, 1995;Nobre & McCarthy, 1994;Van Petten & Luka, 2006), has been viewed as the storage site for long-term semantic knowledge accessed during the bottom-up processing of meaningful stimuli (Badre, Poldrack, PareBlagoev, Insler, & Wagner, 2005;Thompson-Schill, D'Esposito, & Kan, 1999). Enhanced temporal lobe activation has also been found to lexically ambiguous stimuli in some imaging studies, and has been interpreted as reflecting lexico-semantic processing or semantic integration (Gennari, MacDonald, Postle, & Seidenberg, 2007;Rodd, Davis, & Johnsrude, 2005) or consequences of semantic mismatch (Zempleni, Renken, Hoeks, Hoogduin, & Stowe, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…However, our prior work (Lee & Federmeier, 2009), buttressed by neuroimaging findings (Gennari, MacDonald, Postle, & Seidenberg, 2007;Ihara, Hayakawa, Wei, Munetsuna, & Fujimaki, 2007;Rodd, Davis, & Johnsrude, 2005;Zempleni, Renken, Hoeks, Hoogduin, & Stowe, 2007), indicates that multiple neural mechanisms are involved in ambiguity resolution, and that the nature of the information provided by different types of context is important for determining when and how these mechanisms are recruited. The current study was designed to examine whether normal aging imposes differential effects on these subsystems, and, more specifically, to test the hypothesis that the more controlled, topdown, frontal mechanisms important for resolving ambiguity under difficult selection conditions would be more affected by advancing age than the mechanisms used to resolve ambiguity in the presence of biasing semantic supports.…”
Section: Discussionmentioning
confidence: 99%
“…The problem is that the meaning of any particular word is highly confined and constrained by the context of the other words (Gennari et al 2007).…”
Section: Words and Sentences In The Brainmentioning
confidence: 99%